Odpowiedzi

Najlepsza Odpowiedź!
2010-02-28T10:26:43+01:00
A) 2 - 3(4x + 5) = 6x
2-12x-15=6x
-12x-6x=15-2
-18x=13 / : (-18)
x= 13/-18
b) 4x - 5(1 - 2x) = 11
4x-5+10x=11
4x+10x=11+5
14x=16 /:14
x=1¹/₇

c) 20 - 3(x +5) + 5x = 5 - 8x
20- 3x-15+5x=5-8x
-3x+5x+8x=5+15-20
10x =0
x=0




2010-02-28T10:31:45+01:00
A.
2-3(4x+5)=6x
2-12x-15=6x
-12x-6x=15-2
-18x=13/(-180
x=-13/18
b.
4x - 5(1 - 2x) = 11
4x-5+10x=11
14x=11+5
14x=16/14
x=16/14
x=8/7
x=1 i 1/7
c.
20 - 3(x +5) + 5x = 5 - 8x
20-3x-15+5x=5-8x
-3x+5x+8x=5-20+15
10x=0/10
x=0